Dramaturgy as thinking : a Deleuzian approach to thought creation in contemporary theatre forms - Pazgu, Alexandra-Maria; Justus Liebig University Giessen (My University, 2018)
In the contemporary artistic and political context dramaturgy as a practice of content creation is not restricted anymore to the theatre field. Historically, the notion has been applied in the sense of a house dramaturg and referred to as a secondary function in the theatre institution (Luckhurst, 2006; Romanska, 2014). From the perspective of creation processes dramaturgy appears more and more as an individual or collective practice related mostly to devised theatre projects, contemporary dance or interdisciplinary projects. Philosophical and aesthetical approaches, as well as movement related theories and practices have brought a great contribution to the redefinition of dramaturgy as a meaning creation tool in post-narrative interdisciplinary forms. However, most of the approaches concentrate on the process of dramaturgy in the creation stage and exclude the attending process. Even if some approaches define the process dramaturg as the outside eye or the first spectator or the third eye , the complexity of contemporary theatrical devices and the moment of attending can not simply be reduced to the perception of a constructed subjectivity and/or to sign interpretation. Following performance studies scholarship that links performance to philosophy and conceptual thinking, this paper investigates the possibilities of dramaturgy to function as work of actions in the moment of attendance. The main research question considers whether dramaturgy as work of actions may function as thinking and what kind of thinking this would be? In order to answer this question, I start from the hypothesis of a parallel between theatre practice and philosophy via the notions of representation and expression as two different strategies of creating thought and communication. Therefore, dramaturgy is analysed in parallel with a few Deleuzian notions, as a thinking mode, a process of creating thought in the moment of attendance, different from more conventional communication schemes, where meaning is a matter of decoding a specific message. Conventionally, from a dialectical perspective on art (and theatre) as representation of reality, dramaturgy may be viewed as a tool of meaning creation allowing the viewer to ask: what does this mean? In this sense, the notions of dramaturg and dramaturgy may be considered intermediaries between content and expression, artist and viewer, inside and outside. In this process of objectification dramaturgy is concerned, on the one hand, with meaning construction (in the creation process) and, on the other hand, with meaning decoding (from a spectatorial perspective). Alternatively, Deleuze offers a critique of the model of representation, where thinking does not happen anymore via a thinking subject who perceives objects. For Deleuze, thinking is concerned with the process and the connections that escape a juxtaposition of perception and recognition. Following Deleuze, thinking is only happening when there is a clash between form and content. Therefore, the focus is on the potentiality of the performative dispositive to express in case studies that are no longer based on dramatic elements, linearity or any recognizable structure. The examples illustrate new interactions with the Deleuzian thought (e.g. Sensation, Becoming Animal, Affect) and consolidate what Josette Féral (1994) defined as the practico-theoretical research perspective in the arts. Specifically, the analysis focuses on how specific concepts coming from Deleuzian philosophy function in the proximity of dramaturgy as work of actions in the three chosen cases: Boris Nikitin´s Die Sänger ohne Schatten (2014), Antonia Baehr´s Abecedarium Bestiarium (2013) and Ivana Müller´s While we were holding it together (2006). Furthermore, the interest is to analyse dramaturgy as work of actions in the sense of an applied thinking method, and to ask what the specificities of this thinking might be? In this sense, this thesis hopes to bring a contribution to the theory and practice of dramaturgy as a practice of organising thought in artistic practice. Moreover, it may be viewed as an alternative to a mere critique of the theatre mechanism, as a proposal for new ways of thinking in theatre beyond the general gap between theory and practice. The paper aims to influence both attending and creation practices, working and viewing methodologies by shortening the distance between academic research and artistic practice. Also, it hopes to bring a contribution to the newly emerged field of performance philosophy and to other disciplines such as drama studies, theatre studies, performance studies, dance studies and Deleuzian studies.

Im zeitgenössischen künstlerischen und politischen Kontext beschränkt sich die Dramaturgie als Praxis der Inhaltsproduktion nicht mehr auf das Theaterfeld. Historisch wurde der Begriff im Sinne eines Hausdramaturgen angewandt und in der Theaterinstitution als Nebenfunktion bezeichnet (Luckhurst, 2006; Romanska, 2014). Aus der Perspektive der Entstehungsprozesse erscheint Dramaturgie mehr und mehr als individuelle oder kollektive Praxis, die sich meist auf erarbeitete Theaterprojekte, zeitgenössischen Tanz oder interdisziplinäre Projekte bezieht. Philosophische und ästhetische Ansätze sowie bewegungsbezogene Theorien und Praktiken haben einen großen Beitrag zur Neudefinition der Dramaturgie als bedeutungsschaffendem Werkzeug in post-narrativen interdisziplinären Formen geleistet. Die meisten Ansätze konzentrieren sich auf den Prozess der Dramaturgie in der Entstehungsphase und schließen den Prozess der Teilnahme aus. Auch wenn manche Ansätze den Prozessdramaturg als "das äußere Auge" oder "den ersten Betrachter" oder "das dritte Auge" definieren, lässt sich die Komplexität der zeitgenössischen Theatermechanismus und des Moments der Teilnahme nicht einfach auf die Wahrnehmung einer konstruierten Subjektivität reduzieren. Diese Arbeit untersucht die Möglichkeiten der Dramaturgie, im Moment der Teilnahme als work of action (Barba, 2010; Barba & Savarese, 2011) zu definieren. Die Hauptforschungsfrage lautet, ob die Dramaturgie im Sinne der work of actions als Denken funktionieren kann und welche Art von Denken dies wäre. Um diese Frage zu beantworten, gehe ich von der Hypothese einer Parallele zwischen Theaterpraxis und Philosophie aus, über die Begriffe Repräsentation und Expression, als zwei unterschiedliche Strategien des Erschaffens von Denken und Kommunizieren.Daher wird die Dramaturgie parallel zu Deleuze-Begriffen analysiert, als ein Denkmodus, ein Prozess des Erstellens von Gedanken im Moment der Anwesenheit. Diese Perspektive unterscheidet sich von herkömmlichen Kommunikationssystemen, bei denen es um die Entschlüsselung einer bestimmten Sinn geht. Konventionell kann die Dramaturgie aus einer dialektischen Perspektive auf Kunst (und Theater) als Repräsentation der Realität als ein Werkzeug der Bedeutungsbildung betrachtet werden, das dem Betrachter erlaubt zu fragen: Was bedeutet das? In diesem Prozess der Objektivierung befasst sich die Dramaturgie einerseits mit der Bedeutungskonstruktion (im Entstehungsprozess) und andererseits mit der Bedeutungsentschlüsselung (aus der Perspektive des Betrachters). Alternativ bietet Deleuze eine Kritik des Modells der Repräsentation, in der das Denken nicht mehr über ein denkendes Subjekt geschieht, das Objekte wahrnimmt. Für Deleuze geht es beim Denken um den Prozess und die Verbindungen, die einer Gegenüberstellung von Wahrnehmung und Wiedererkennung entgehen. Nach Deleuze geschieht das Denken nur, wenn es einen Konflikt zwischen Form und Inhalt gibt. Im Fokus steht daher die Möglichkeit, dass das performative Dispositiv zum Ausdruck kommt in Fallstudien die nicht mehr auf dramatischen Elementen, Linearität oder erkennbaren Strukturen basieren. Die Beispiele illustrieren neue Interaktionen mit dem Konzepte aus der Deleuze´schen Philosophie (z. B. Sensation, Becoming Animal, Affekt etc.) und konsolidieren, was Josette Féral (1994) als die "praktisch-theoretische" Forschungsperspektive in den Künsten definierte.Konkret geht es darum zu untersuchen, wie spezifische Konzepte der Deleuze´schen Philosophie im Sinne der Dramaturgie als work of actions in den drei ausgewählten Beispielen funktionieren: Boris Nikitin´s "Die Sänger ohne Schatten" (2014), Antonia Bähr´s "Abecedarium Bestiarium" (2013) und Ivana Müller´s "While we were holding it together" (2006). Darüber hinaus soll die Dramaturgie als work of actions im Sinne einer angewandten Denkmethode analysiert und nach den Besonderheiten dieses "Denkens" gefragt werden. In diesem Sinne hofft diese Arbeit, einen Beitrag zur Theorie und Praxis der Dramaturgie als einer Praxis des Organisierens von Denken in der künstlerischen Anwendung zu leisten. Darüber hinaus kann die vorliegende Arbeit als eine Alternative zu einer bloßen Kritik am Theatermechanismus betrachtet werden, als ein Vorschlag für neue Denkweisen im Theater jenseits der allgemeinen Kluft zwischen Theorie und Praxis. Die Arbeit zielt darauf ab, sowohl die Teilnahme als auch die Kreationspraktiken, Arbeits- und Betrachtungsmethoden zu beeinflussen, indem die Distanz zwischen akademischer Forschung und künstlerischer Praxis verkürzt wird. Außerdem möchte sie einen Beitrag zu dem neu entstandenen Bereich der Performance Philosophy und zu anderen Disziplinen wie Drama Studies, Theatre Studies, Performance Studies, Dance Studies und Deleuzian Studies leisten.
Keywords: Dramaturgie; Deleuze; Aufführungsanalyse; Performativität; Drama; Denken; Aktion; Akt; Repräsentation; Differenz; dramaturgy; performative; performance philosophy; deleuze; drama; action; thinking; attendance; representation; expression; ddc:792